2022
DOI: 10.1111/ene.15561
|View full text |Cite
|
Sign up to set email alerts
|

Batoclimab as an add‐on therapy in neuromyelitis optica spectrum disorder patients with acute attacks

Abstract: Neuromyelitis optica spectrum disorder (NMOSD) is a rare neurological inflammatory disorder, characterized by recurrent myelitis and optic neuritis, which can lead to severe paralysis and blindness.It is reported that more than 75% of NMOSD patients are seropositive for aquaporin-4 immunoglobulin G (AQP4-IgG) [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Other experimental therapy approaches, such as intravenous immunoglobulins (IVIG), early anti-CD20 therapy, and early anti-complement therapy, have been reported in single case series to possibly lead to favorable outcomes in acute attacks [ 65 , 127 , 132 , 147 ]. Future therapies may also include antibodies against the neonatal Fc receptor, which are currently being studied in an open-label trial [ 236 , ClinicalTrials.gov].
Fig.
…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…Other experimental therapy approaches, such as intravenous immunoglobulins (IVIG), early anti-CD20 therapy, and early anti-complement therapy, have been reported in single case series to possibly lead to favorable outcomes in acute attacks [ 65 , 127 , 132 , 147 ]. Future therapies may also include antibodies against the neonatal Fc receptor, which are currently being studied in an open-label trial [ 236 , ClinicalTrials.gov].
Fig.
…”
Section: Treatment Of Nmosd: General Aspects and Outcome Measuresmentioning
confidence: 99%
“…The patient experienced no adverse events during or subsequent to treatment. Earlier studies have demonstrated that the addition of the FcRn-monoclonal antibody, Batoclimab, to IVMP therapy enhances the EDSS scores in patients with acute NMOSD within 3–6 months [ 15 ]. Thus, FcRn antagonists are probably beneficial not only during the acute phase of NMOSD but may also contribute to sustained neurological function improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The drug is undergoing phase II trials for Myasthenia Gravis and currently utilised in Neuromyelitis Optica. In TED it may decrease circulating TSHR and IGF-1 antibodies [ 146 , 147 ].…”
Section: Targeting Components Of the Inflammatory Cascadementioning
confidence: 99%